Navigating the EU Flood Directive Adoption in Montenegro: Challenges, Gaps, and Pathways for Improvement - Ostojic , Milena; Sekulic, Goran; Cipranic, Ivana (European Journal of Sustainable Development, 2025)
Montenegro, as a candidate country for European Union accession, has undertaken the process of aligning its flood risk management framework with the EU Floods Directive (2007/60/EC). This paper examines the challenges and obstacles encountered in different stages of this process, including Preliminary Flood Risk Assessment, Flood Hazard and Fisk Mapping, and the development of Flood Risk Management Plans. It begins with an overview of Montenegro’s flood-related legislation before the adoption process, highlighting key shortcomings in regulatory and institutional frameworks. The paper then outlines the steps taken to implement the Directive, identifying difficulties related to data availability, institutional coordination, financial constraints, and technical expertise. Despite efforts to enhance flood risk management, challenges remain in integrating it effectively into national policies and practices. By analyzing these challenges, the paper provides insights into opportunities for improvement and potential lessons for other candidate countries facing similar requirements. The findings contribute to the broader discussion on disaster risk reduction and sustainable flood management in transitioning economies, emphasizing the importance of institutional capacity, long-term planning, and regional cooperation in implementing EU environmental policies. Keywords: EU Floods Directive, Flood Risk Management, Disaster Risk Reduction, Policy Implementation